Evapotranspiration and Runoff Patterns Across California's Sierra Nevada - Rungee, Joseph; Ma, Qin; Goulden, Michael L.; Bales, Roger (Frontiers in Water, 2021)
Spatially resolved annual evapotranspiration was calculated across the 14 main river basins draining into California’s Central Valley, USA, using a statistical model that combined satellite-greenness, gridded-precipitation, and flux-tower measurements. Annual evapotranspiration across the study area averaged 529 mm. Average basin-scale annual precipitation minus evapotranspiration was in good agreement with annual runoff, with deviations in wet and dry years suggesting withdrawal or recharge of subsurface water storage. Evapotranspiration peaked at lower elevations in the colder, northern basins, and at higher elevations in the southern high-Sierra basins, closely tracking the 12.3 °C mean temperature isocline. Precipitation and evapotranspiration are closely balanced across much of the study region, and small shifts in either will cause disproportionate changes in water storage and runoff. The majority of runoff was generated below the rain-snow transition in northern basins, and originated in snow-dominated elevations in the southern basins. Climate warming that increases growing season length will increase evapotranspiration and reduce runoff across all elevations in the north, but only at higher elevations in the south. Feedback mechanisms in these mountain basins, plus over-year subsurface storage, with their steep precipitation and temperature gradients, provide important buffering of the water balance to change. Leave-one-out cross validation revealed that the statistical model for annual evapotranspiration is sensitive to the number and distribution of measurement sites, implying that additional strategically located flux towers would improve evapotranspiration predictions. Leave-one-out with individual years was less sensitive, implying that longer records are less important. This statistical top-down modeling of evapotranspiration provides an important complement to constraining water-balance measurements with gridded precipitation and unimpaired runoff, with applications such as quantifying water balance following forest die-off, management or wildfire.